Spinal TNF-α receptor 1 is differentially required for phrenic long-term facilitation (pLTF) over the course of motor neuron death in adult rats - Lewis, Ryan D.; Keilholz, Amy N.; Smith, Catherine L.; Burd, Ethan A.; Nichols, Nicole L. (Frontiers in Physiology, 2024)
IntroductionIntrapleural injections of cholera toxin B conjugated to saporin (CTB-SAP) result in selective respiratory (e.g., phrenic) motor neuron death and mimics aspects of motor neuron disease [(e.g., amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA)], such as breathing deficits. This rodent model allows us to study the impact motor neuron death has on the output of surviving phrenic motor neurons as well as the compensatory mechanisms that are recruited. Microglial density in the phrenic motor nucleus as well as cervical gene expression of markers associated with inflammation (e.g., tumor necrosis factor α; TNF-α) are increased following CTB-SAP-induced phrenic motor neuron death, and ketoprofen (nonsteroidal anti-inflammatory drug) delivery attenuated phrenic long-term facilitation (pLTF) in 7 day (d) CTB-SAP rats but enhanced pLTF in 28d CTB-SAP rats.MethodsHere, we worked to determine the impact of TNF-α in the phrenic motor nucleus by: 1) quantifying TNFR1 (a high affinity transmembrane receptor for TNF-α) expression; 2) investigating astrocytes (glial cells known to release TNF-α) by performing a morphological analysis in the phrenic motor nucleus; and 3) determining whether acute TNFR1 inhibition differentially affects phrenic plasticity over the course of CTB-SAP-induced motor neuron loss by delivering an inhibitor for TNF-α receptor 1 (sTNFR1i) in 7d and 28d male CTB-SAP and control rats.ResultsResults revealed that TNFR1 expression was increased on phrenic motor neurons of 28d CTB-SAP rats (p < 0.05), and that astrocytes were increased and exhibited reactive morphology (consistent with an activated phenotype; p < 0.05) in the phrenic motor nucleus of CTB-SAP rats. Additionally, we found that pLTF was attenuated in 7d CTB-SAP rats but enhanced in 28d CTB-SAP rats (p < 0.05) following intrathecal sTNFR1i delivery.ConclusionThis work suggests that we could harness TNFR1 as a potential therapeutic agent in CTB-SAP rats and patients with respiratory motor neuron disease by increasing compensatory plasticity in surviving neurons to improve phrenic motor neuron function and breathing as well as quality of life. Future studies will focus on microglial and astrocytic cytokine release, the role they play in the differential mechanisms of pLTF utilized by 7d and 28d CTB-SAP rats, and potential therapies that target them.